Tax evasion and its incidence in the economy of Ecuador, 2010-2014 - Zamora Cusme, Yesenia (2018)
The article analyzes tax evasion and its incidence in the economy of Ecuador, in the period 2010-2014, Ecuador has a strengthened tax system due to policies implemented by the Government in recent years, however there are gaps in tax collection. One of the main problems that affect and prevent this process is effective tax evasion by taxpayers, this being a determinant in tax resources, failure to pay taxes causes scarcity of wealth and -above all-the economic and social structure of the country deteriorates. Based on the problem, a non-experimental, bibliographic, qualitative, qualitative, correlational and cross-sectional study of the variables was carried out. As main results, we obtained that the policies adopted by Ecuador based on taxes and the constant ignorance of the norms are causes of evasion, as well as the lack of tax culture, and the perception that there is a low risk of being detected are factors that reduce the collection of taxes in Ecuador, a factor that directly influences the economy of the country in this period.